Clinicopathological significance and diagnostic approach of ROS1 rearrangement in non-small cell lung cancer: a meta-analysis: ROS1 in non-small cell lung cancer. Issue 4 (November 2018) - Yang, Jungho; Pyo, Jung-Soo; Kang, Guhyun
Purpose: The aim of this study was to investigate the rate of ROS1 rearrangement and concordance between ROS1 immunohistochemistry (IHC) and molecular tests in non-small cell lung cancer (NSCLC). Methods: The study included 10, 898 NSCLC cases from 21 eligible studies. ROS1 rearrangement rates were evaluated in NSCLC by a meta-analysis, including subgroup analyses. In addition, we performed a concordance analysis and a diagnostic test accuracy review of ROS1 IHC in NSCLC. Results: The estimated overall rate of ROS1 rearrangement and IHC positivity was 2.4% (95% confidence interval (CI) 1.5, 3.7). In the subgroup analysis, which was based on tumor subtype, the rate of ROS1 rearrangement and IHC positivity was 2.9% (95% CI 1.9, 4.5) and 0.6% (95% CI 0.3, 1.2) in adenocarcinoma and non-adenocarcinoma, respectively. The overall concordance rate between ROS1 IHC and molecular tests was 93.4% (95% CI 78.3, 98.2). In ROS1 IHC positive and negative cases, the concordance rates were 79.0% (95% CI 43.3, 94.9) and 97.0% (95% CI 83.3, 99.5), respectively. The pooled sensitivity and the specificity of ROS1 IHC were 0.90 (95% CI 0.70, 0.99) and 0.82 (95% CI 0.79, 0.84), respectively. The diagnostic odds ratio and the area under the curve of the summary receiver operating characteristic curve were 118.01 (95% CI 11.81, 1179.67) and 0.9417, respectively. Conclusion: The rates of ROS1 rearrangement differed by tumor histologic subtype in NSCLC. ROS1 IHC may be useful for the detection of ROS1 rearrangement in NSCLC. Detailed criteria for evaluating ROS1 IHC are needed before it can be applied in daily practice.